2019
DOI: 10.5761/atcs.oa.18-00188
|View full text |Cite
|
Sign up to set email alerts
|

Safety Pericardiocentesis with Fluoroscopy Following Cardiac Surgery

Abstract: Purpose: In the treatment of the postsurgical pericardial effusions via pericardiocentesis, determination of the puncture site might be difficult. Contrast echocardiography may not be efficient due to surgical artefacts and pulmonary problems and therefore may lead to inaccurate evaluation. Alternative imaging methods might be helpful to perform the pericardiocentesis with decreased complications. Methods: We retrospectively analyzed the patients who had undergone pericardiocentesis in our departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…It is considered a very safe procedure, is usually preceded by echocardiographic visualization, and is performed via the subxiphoid approach. In a study by Ibrahim et al, the incidence of complications seen with fluoroscopic guidance was close to zero [11]. However, this procedure is performed only in the catheterization lab and involves exposing the patient and the physician to significant radiation.…”
Section: Discussionmentioning
confidence: 98%
“…It is considered a very safe procedure, is usually preceded by echocardiographic visualization, and is performed via the subxiphoid approach. In a study by Ibrahim et al, the incidence of complications seen with fluoroscopic guidance was close to zero [11]. However, this procedure is performed only in the catheterization lab and involves exposing the patient and the physician to significant radiation.…”
Section: Discussionmentioning
confidence: 98%
“…Safe patient positioning involves balancing procedural comfort and optimal procedural setting against the risks related to the patient position 26 . Ibrahim et al reported successful echocardiography and fluoroscopy guided postoperative pericardiocentesis with the patient in slightly semi‐seated position 27 . Mitsuda et al reported successful US‐guided peripherally inserted central catheter (PICC) in a patient with congestive heart failure in the sitting position 28 .…”
Section: Discussionmentioning
confidence: 99%
“… 26 Ibrahim et al reported successful echocardiography and fluoroscopy guided postoperative pericardiocentesis with the patient in slightly semi‐seated position. 27 Mitsuda et al reported successful US‐guided peripherally inserted central catheter (PICC) in a patient with congestive heart failure in the sitting position. 28 This technique of inserting a drainage in a patient who has assumed the sitting position is simple and feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopy guided pericardiocentesis is performed in the catheterisation laboratory -most commonly for iatrogenic pericardial effusions that occur during interventional procedures or cardiac surgery [21,22]. Injection of contrast through the needle tip followed by radiographic imaging can be used to assess needle tip position relative to the pericardial space.…”
Section: Fluoroscopymentioning
confidence: 99%